Hospitalist intervention for appropriate use of telemetry reduces length of stay and cost. Issue 9 (7th July 2015) - Svec, David; Ahuja, Neera; Evans, Kambria H.; Hom, Jason; Garg, Trit; Loftus, Pooja; Shieh, Lisa
<x xml:space="preserve">Abstract</x> BACKGROUND Telemetry monitoring is a widely used, labor‐intensive, and often‐limited resource. Little is known of the effectiveness of methods to guide appropriate use. OBJECTIVE Our intervention for appropriate use included: (1) a hospitalist‐led, daily review of bed utilization, (2) hospitalist‐driven education module for trainees, (3) quarterly feedback of telemetry usage, and (4) financial incentives. DESIGN/METHODS Hospitalists were encouraged to discuss daily telemetry utilization on rounds. A module on appropriate telemetry usage was taught by hospitalists during the intervention period (January 2013–August 2013) on medicine wards. Pre‐ and post‐evaluations measured changes regarding telemetry use. We compared hospital bed–use data between the baseline period (January 2012–December 2012), intervention period, and extension period (September 2014–March 2015). During the intervention period, hospital bed–use data were sent to the hospitalist group quarterly. Financial incentives were provided after a decrease in hospitalist telemetry utilization. SETTING Stanford Hospital, a 444‐bed, academic medical center in Stanford, California. RESULTS Hospitalists saw reductions for both length of stay (LOS) (2.75 vs 2.13 days, P = 0.005) and total cost (22.5% reduction) for telemetry bed utilization in the intervention period. Nonhospitalists telemetry bed utilization remained unchanged. We saw significant improvements in trainee knowledge of the most cost‐saving action (P = 0.002) and the least cost‐saving action (P = 0.003) in the pre‐ and post‐evaluation analyses. Results were sustained in the hospitalist group, with telemetry LOS of 1.93 days in the extension period. CONCLUSIONS A multipronged, hospitalist‐driven intervention to improve appropriate use of telemetry reduces LOS and cost, and increases knowledge of cost‐saving actions among trainees. Journal of Hospital Medicine 2015;10:627–632. © 2015 Society of Hospital Medicine